A review on copper oxide thin films - Ho, Soon Min (International Journal of Recent Scientific Research, 2016)
Copper oxide films have direct band gap of about 1.2 to 2.6eV. They could be used in many applications including solar cell, sensor and optoelectronic industry. The aim of this work is to investigate the properties of copper oxide thin films under various deposition methods. The obtained results based on the structure, optical, morphology and electrical properties are discussed. The overall results found that different researchers have reported different properties of copper oxide based on experimental conditions.